RESEARCH PRODUCTIVITY FACTORS IN THE GOVERNMENT INSTITUTIONS (STUDY IN THE OFFICE OF RESEARCH AND DEVELOPMENT AND TRAINING, MINISTRY OF RELIGIOUS AFFAIRS OF INDONESIA) - Saimroh, Saimroh (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
The Productivity of Indonesian researchers is still considered low at the international level. The researcher productivity is measured through the amount of scientific papers published. This study aimed to prove some factors affecting the research productivity. Specifically, this study aimed to empirically examine the effect of researcher characteristics, subjective well-being, knowledge sharing, and research competence on research productivity.With stratified proportional random sampling technique we obtained a sample of 100 researchers in Office of Research and Development and Training scattered in central and local units. Data were collected using questionnaires to measure research productivity, subjective well-being, knowledge sharing, and research competence. Data were analyzed descriptively and inferentiallly. We used analysis of variance (ANOVA) and path analysis which were processed with SPSS 16 and LISREL 8.80 (Student) for the inferential analysis. The results of ANOVA concluded that the productivity did not differ significantly by gender. However there were significant differences in the research productivity based on the academic qualification and the functional job of researchers. The results of path analysis concluded that subjective well-being and research competence had direct positive effect on the research productivity, knowledge sharing had direct negative impact on the research productivity but knowledge sharing had indirect positive effect through the research competence on the research productivity. Research compentence contributes the highest effect on the research productivity. From this study we recommend that the institution need to improve the research competence on quantitative research method with regard to statistical tools to collect, process, and analyze the research data.